Quality characteristics and thermal behavior of buriti (Mauritia flexuosa L.) oil - Freitas, M. L.F. [UNESP]; Chisté, R. C.; Polachini, T. C. [UNESP]; Sardella, L. A.C. [UNESP]; Aranha, C. P.M.; Ribeiro, A. P.B.; Nicoletti, V. R. [UNESP] (My University, 2017)
This work reports a complete characterization of buriti oil. Physicochemical properties were determined according to AOCS methodologies and thermophysical properties were measured using a controlled stress rheometer and a digital electronic density meter. ?-carotene and tocopherol contents were obtained using HPLC systems. Fatty acids and acylglycerol classes were determined using GC and HPSEC systems, respectively, while triacylglycerol composition was estimated using the software PrOleos. Thermal behavior (crystallization and melting) was analyzed using a DSC. The results attested high levels of total carotenoids with ?-carotene as the major one; total tocopherols contained ?- and ?-tocopherols which accounted for 91% of the total; and monounsaturated fatty acids were mainly represented by oleic acid. The results showed close agreement between density and viscosity of buriti and olive oils. The crystallization and melting peaks occurred at -43.06 °C and -2.73 °C, respectively. These properties enable Buriti oil to be recommended as an excellent alternative for enriching foods with bioactive compounds.
Keywords: ?-carotene; Carotenoids; Monounsaturated fatty acid; Oleic acid; Tocopherols; Triunsaturated triacylglycerols